Zākira Husaina : adhyāpaka jo rāshṭrapati pada para huā āsīna - Husain, Zakir, 1897-1969.; Riz̤vī, Mujīb; Hameed, Syeda Saiyidain; Indian Council for Cultural Relations (Naī Dillī : Bhāratīya Sāṃskr̥tika Sambandha Parishada, 2000)
Contributed articles on the life and work of Zakir Husain, 1897-1969, former president of India; includes briefly articles and transcript of lectures by him; commemorative volume published on the occasion of his birth centenary.
"Śatābdī granthāvalī"--Spine.
Includes bibliographical references.
Mode of access: Internet.
In Hindi.
Keywords: Husain, Zakir, -- 1897-1969.; Presidents -- India -- Biography